Incidence and Patterns of Representation Campaign Tactics: A Comparison of Manufacturing and Service Unions - Reed, Thomas (Relations industrielles / Industrial Relations, 1992)
Using data on 430 campaigns provided by organizers employed by eight U.S. unions, this paper examines the incidence and patterns of organizing tactics in representation campaigns. Three issues are addressed: how prévalent are various organizing strategies and tactics?; do tactics differ by union type?; and do patterns exist among campaign tactics?